Estimation the reliability function of multi state system by using Direct Partial Logic Derivative - فدعم انتصار عريبي; داود اسيل مبدر (Journal of Economics and Administrative Sciences, 2014)
In this research is estimated the function of reliability dynamic of multi state systems and their compounds and for three types of systems (serial, parallel, 2-out-of-3) and about two states (Failure and repair) depending on calculating the structur function allow to describing the behavior of the reliability of the system depending on the efficiency of its components. And the researcher estimates the dynamic reliability indicators which in turn describes changes in the reliability of multi state system caused by changes in the efficiency of the components system. These indicators were estimated by Direct Partial Logic derivative Sampeles:- (MSS): Multi-state system (MSSRF) : Reliability function of Multi-state system Φ(x): Structure function (SFOMSS): Structure function of Multi-state system (DRI): Dynamic Reliability Indices Gf/Xi:set of failure states for each compmnent Gr/Xi: set of repair states for each compmnent (CDRI): Dynamic reliability for each component (DIRI): Dynamic reliability for complete system